Pengembangan E-LKPD dengan Model Discovery Learning Pada Kurikulum Merdeka Kelas IV SD - Nurfadilah, Sani Sarah; Puspitasari, Ina; Indrianingsih, Reva; Wardah, Sansan Khaulatul; Nuryadin, Asep (Dawuh Guru: Jurnal Pendidikan MI/SD, 2025)
This research aims to develop interactive E-LKPD that allows students to learn material on changes in the state of matter for grade IV Elementary School students using the discovery learning model. The research employed the Research and Development (R&D) with the ADDIE approach, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 23 students from an elementary school in Tasikmalaya Regency. The initial phase involved a needs analysis to determine the design and development of the E-LKPD. The interactive E-LKPD was designed with features such as reading materials, instructional videos, images, drag-and-drop functionality, educational games, and practice exercises. The results of the study showed that students' responses to the use of the E-LKPD were very positive, with an average response score of 92.17%. The main advantages are its ability to make learning more engaging, motivate, support active and independent learning. Although there are technical constraints such as internet connectivity and limited devices, solutions such as tethering and group work have succeeded in overcoming them and this E-LKPD can be printed according to school needs. The development of this E-LKPD aligns with the demands of the digital era and the implementation of the Kurikulum Merdeka and has proven effective in enhancing the teaching and learning of IPAS in elementary schools.